Gender differences in self-reported health - the significance of inequality in domestic work. (13th November 2019) - Nyman, C Staland; Hensing, G
Abstract: Background: Gender difference in health is an important public health issue. Although biological factors contribute, social processes and living conditions create, maintain and exacerbate health differences between women and men. The aim of this study was to examine if lack of equality in domestic work contributes to the explanation of gender differences in self-reported mental well-being, common symptoms and persistent illness. Methods: Population based questionnaire data on co-habiting women and men in Sweden, aged 19-64 years (n = 2666), was used. Division of planning and performing domestic work, satisfaction with division of domestic work and equality in partner relationship, were analysed in relation to health outcomes using binary logistic regression analysis with adjustments for age, income, country of birth, occupational class, weekly hours in paid work and number of children. Results: Women, compared to men, showed higher odds (OR) for having low mental well-being, OR 1.35 (1.07-1.70), > 7 common symptoms, OR 1.98 (CI 1.59-2.46) and ≥ 1 persistent illness, OR 1.25 (CI 1.06-1.47). When equal partner relationship and planning and performing domestic work were included in the regression, the ORs for mental well-being and persistent illness slightly weakened and decreased to non-significance when satisfaction with division of domestic work were analysed, OR 1.14 (0.99-1.44) and OR 1.18 (0.99-1.39) respectively. Corresponding ORs for common symptoms were almost unchanged throughout the analysis. Conclusions: Satisfaction with division of domestic work contributed to explanation of gender differences in persistent illness and notably to differences in mental well-being. Key messages: Inequality in domestic work could contribute to explanation of gender difference in health. Satisfaction in division of domestic work is of specific relevance in gender difference in mental health.